Straightforward measurement of anisotropic thermal properties of a Bi2Se3 single crystal. (22nd February 2018) - Fournier, D; Marangolo, M; Eddrief, M; Kolesnikov, N N; Fretigny, C
Abstract: We demonstrate here a simple measurement protocol which allows the thermal properties of anisotropic crystalline materials to be determined. This protocol is validated by the measurement of Bi2 Se3, a layered material consisting of covalently bonded sheets with weak van der Waals bonds between each layer, which has highly anisotropic thermal properties. Thermoreflectance microscopy measurements were carried out on a single-crystal Bi2 Se3 sample, firstly on the bare sample and then after capping with a 100 nm thick gold layer. Whereas on the bare sample lateral heat diffusion is dominated by the in-plane thermal diffusivity, on the metal-capped substrate heat diffusion perpendicular to the sample surface dominates. Using a simple theoretical model, we show how this double measurement protocol allows the anisotropic thermal conductivity coefficients of bulk Bi2 Se3 to be evaluated.